Ligand-Free Nickel-Catalyzed Reductive Allylic Defluorinative Cross-Coupling of α-Trifluoromethyl Alkenes with Epoxides - Lin, Zhiyang; Lan, Yun; Wang, Chuan (Synlett, 2020)
We report a reductive allylic defluorinative reaction of α-trifluoromethyl alkenes with terminal epoxides, which consists of an iodide-mediated regioselective ring opening and a nickel-catalyzed radical-type cross-coupling, providing diverse tertiary gem-difluorobishomoallylic alcohols in moderate to high yields. Notably, this reaction is conducted under mild conditions and requires no external ligand or proton donor.
Keywords: nickel catalysis; epoxides; difluoroalkenes; defluorination; ring opening